O experimento e o lúdico: reflexões sobre atividades didáticas experimentais para o ensino de Física e a ludicidade - Sartorello, João Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
In this work, is discussed the importance of experimental activities in Education of Physics in Basic Education from the experience of Supervised Stage and the work with the Initiation of Teaching in the Program PIBID CAPES, in this case linked to the Department of Education of the Institute of Biosciences, Campus Rio Claro, São Paulo State, in partnership with three schools of basic education in the city. At first, based on the work of Ferreira with Instrumentation for Teaching Physics, consider the electrostatic theme. The focus is the searching for equipments constructed with low cost materials and easy access. Were developed and promoted strategies of the use of such materials in Physics’ Teaching, with a view to reintroducing experimental teaching activities in Public Basic Education, in the form Workshop Learning and Teaching of Physics, as well as lessons of Laboratory with the help of script and also in the form of an Experiments Library. These experimental activities were critically analyzed with a focus on playfulness. The focus of work in experimental activities for the Physics’ Teaching allowed to redeem, critically, didactic materials. From the standpoint of playfulness, playful moments and interaction of individuals with the knowledge that provides the experimental material when used strategically, they seem to be of great relevance to the Physics’ Teaching in Basic Education. It is possible to use experiments in Physics’ Teaching in public schools

Neste trabalho, discute-se a importância das atividades experimentais para o Ensino de Física na Educação Básica a partir da experiência do Estágio Supervisionado e do trabalho com a Iniciação a Docência no âmbito do Programa PIBID CAPES, neste caso o vinculado ao Departamento de Educação do Instituto de Biociências, no Campus de Rio Claro, Estado de São Paulo, em parceria com três escolas da Educação Básica da cidade. Inicialmente, baseados no trabalho de Ferreira com Instrumentação para o Ensino de Física, consideramos a temática Eletrostática. Privilegia-se a busca por equipamentos que possuam em sua construção materiais de baixo custo e fácil acesso. Foram elaboradas e promovidas estratégias de uso de tais materiais experimentais no Ensino de Física, tendo em vista a reintrodução de atividades didático experimentais na Educação Básica Pública, na forma de Oficinas de Aprendizagem e Ensino de Física, bem como em aulas de Laboratório com auxílio de roteiro e ainda na forma de uma Biblioteca de Experimentos. Tais atividades experimentais foram criticamente analisadas sob o enfoque da ludicidade. O foco do trabalho em atividades experimentais para o Ensino de Física permitiu resgatar, de forma crítica, materiais didáticos. Do ponto de vista da ludicidade, os momentos lúdicos e a interação dos sujeitos com o conhecimento, que o material experimental proporciona quando estrategicamente utilizado, parecem ser de grande pertinência para o Ensino de Física na Educação Básica. É possível a utilização de experimentos didáticos no Ensino de Física na rede Pública de Ensino
Keywords: Física - Estudo e ensino; Eletrostatica; Laboratorios de fisica; Laboratórios experimentais; Fisica experimental; Material didático; Physics - Study and teaching; Physical laboratories; Testing laboratories; Electrostatics; Physics - Experiments